Planning and economic policy in India - Gadgil, D. R. (Poona: Gokhale Institute of Politics and Economics, New York, Asia Pub. House, 1961)
This book gives an idea to the economists in India, advertising government in connection with planning, works or has to work
Bibliographical index
MF22/01/2019
Loans
Keywords: Economic policy - India; Economic planning; India